CMTM6 and CMTM4 as two novel regulators of PD-L1 modulate the tumor microenvironment - Zhang, Tong; Yu, Haixiang; Dai, Xiangpeng; Zhang, Xiaoling (Frontiers in Immunology, 2022)
The tumor microenvironment (TME) plays crucial roles in regulating tumor occurrence, progress, metastasis and drug resistance. However, it remains largely elusive how the components of TME is regulated to govern its functions in tumor biology. Here, we discussed how the two novel functional proteins, chemokine-like factor (CKLF)-like MARVEL transmembrane domain-containing 6 (CMTM6) and CMTM4, which involved in the post-translational regulation of PD-L1, modulate the TME functions. The roles of CMTM6 and CMTM4 in regulating TME components, immune cells and tumor cells themselves were discussed in this review. The potential clinical applications of CMTM6 and CMTM4 as biomarkers to predict therapy efficacy and as new or combined immunotherapy targets are also highlighted. Finally, the current hot topics for the biological function of CMTM6/4 and several significant research directions for CMTM6/4 are also briefly summarized in the review.